Effort regulation in rowing races depends on performance level and exercise mode - Brown, M. R.; Delau, S.; Desgorces, F. D. (Journal of Science and Medicine in Sport, 2010)
This study investigated the influence of performance level and exercise mode on the rowers` pacing strategies. On-water and indoor split times and placements (every 500-m) were obtained from individual 2000-m performances set at the elite, national and sub-elite competitive levels. The data was sorted into indoor (n = 580) and on-water exercises (n = 507). Indoor and on-water strategies statistically differed, whatever the competition level (p < 0.001). Analysis of absolute and normalised velocities demonstrated higher and steadier paces in elite races compared to national and sub-elite races (p < 0.001). On water, intermediate placements highlighted the great influence of taking the front of the race particularly at the elite level (at the elite level 78% of the winners were first at the middle of the race and 100% were in the first three). A "parabolic-shaped" profile could describe all races but performance level and exercise mode may alter this effort regulation to even (elite races) or positive paces (national and sub-elite indoor races). The even paces reported as the optimal strategy were not observed in lower performance levels probably because of rowers` inability to combine higher physiological effort and technical requirements of on-water rowing. Training exercise may account for these paces differences, according to the athletes` competitive level and to exercise mode.